Variations in the physicochemical properties of soil, enzyme activities, and the characteristics of bacterial communities within algal biocrusts and subsoils across different plant communities - Haonian Li; Zhongju Meng; Xiaomen Ren; Yanlong Han (Global Ecology and Conservation)
Algal biological soil crusts (ABSCs) as ecological engineers inhabiting the soil-atmosphere boundary in dryland. Bacteria living at this boundary drive the diversity of ecosystem functions and services. However, it is still unknown whether differences in vegetation communities drive differences in soil bacterial communities, soil physicochemical properties, and enzyme activities in ABSCs and subsoils. Soil samples were collected from sites with and without algal crusts in the vicinity of shrub canopies within two representative plant communities (i.e., Salix psammophila and Hedysarum scoparium), in the Hobq Desert, as well as from mobile sandy lands. We collected soil from the 0–2 cm (including the crust layer), 2–5 cm, and 5–10 cm soil layers, and measured and analyzed the soil physicochemical properties, enzyme activity and soil bacterial community characteristics. Our results showed that there were significant differences in soil physicochemical properties, enzyme activities, and bacterial community diversity in the 0–2 cm soil layer among ABSCs plots with different plant communities. Compared with mobile sandy land, the ABSCs in different vegetation communities significantly increased soil nutrient levels, enzyme activities, and diversity of soil bacterial communities. It is noteworthy that ABSCs exerted a beneficial influence on the soil quality of the 0–2 cm layer, yet simultaneously reduced the relative abundance and diversity index of the soil bacterial community, in comparison to plots devoid of ABSCs within the same plant community. In addition, the ABSCs differed in the network topological characteristics of soil bacterial communities in different plant communities. Specifically, the ABSCs positively promote relationships between soil bacterial genera yet reduce the complexity of bacterial communities. Among them, the ABSCs in the community of H. scoparium are not conducive to forming bacterial network modularity (Modularity= 0.336 < 0.4). Our results highlight that the ABSCs in different plant communities have an impact on the variation in soil bacterial community structure factors. These insights are pivotal for understanding the impacts of plant community-driven ABSCs on soil bacterial communities, particularly in the context of global climate change and persistent drought conditions.